The environmental Kuznets curve in Japan with nuclear energy and foreign direct investment using ARDL and NARDL models - Abdul Hayy Haziq, Mohamad; Mohd Shahidan, Shaari (Springer Nature, 2025)
This study investigates the relationship between carbon dioxide (CO2) emissions, economic growth, nuclear energy, and foreign direct investment (FDI) in Japan over the period 1985–2023. Employing autoregressive distributed lag (ARDL) and nonlinear ARDL (NARDL) models, it tests the Environmental Kuznets Curve (EKC) hypothesis and explores both linear and asymmetric dynamics. The results confirm the EKC pattern, showing that economic growth initially raises emissions but reduces them beyond a critical income threshold. Nuclear energy is found to significantly lower CO2 emissions, underscoring its role as a low-carbon energy source, although transitional adjustment costs are observed in the short run. By contrast, FDI exerts a small but positive influence on emissions, suggesting that capital inflows may contribute to environmental pressures in the absence of strict regulatory oversight. These findings highlight the importance of stable nuclear energy policies, enhanced green investment screening, and integrated energy strategies for achieving Japan’s carbon neutrality targets. This research contributes new evidence by jointly analysing GDP, nuclear energy, and FDI within the EKC framework and by applying asymmetric methods to capture Japan’s post-Fukushima energy transition.